GEOCHEMICAL ASSESSMENT OF THE POTENTIALLY TOXIC ELEMENTS BACKGROUND CONTENTS IN SOILS IN THE AREA OF THE SARALA GOLD ORE CLUSTER (THE REPUBLIC OF KHAKASSIA, RUSSIA) - I. N. Myagkaya; I. S. Kirichenko; B. Yu. Saryg-ool; M. A. Gustaitis (Геодинамика и тектонофизика, 2022)
We assessed the contents of Fe, Ni, Cu, Zn, As, Cr, Pb, Hg in soils of the residential settlements and surrounding areas exposed to anthropogenic load due to mining activities. The study object is located in the Kuznetsk Alatau (part of the Sarala gold ore cluster – SGOC), the village of Priiskovy and its tailings dump, the village of Ordzhonikidzevsky, the Republic of Khakassia). The background contents in the SGOC soils are the following: Fe 3.08–5.06 %, Ni 24.74–45.13 g/t, Cu 22.33–38.81 g/t, Zn 86.72–200 g/t, As 5.45–11.25 g/t, Cr 35.60–73.25 g/t, Pb 14.12–26.17 g/t, Hg 0.01–0.14 g/t. It was found that the background area has increased the natural contents of the studied elements. The soils sampled from the territory of the tailing dump are distinguished by the elevated element contents relative to the background values and especially by a sharp jump of the As and Zn contents (abnormal contents). The contents of all the elements examined in the soils of the territories in the vicinity of the tailing dump also exceed the background values of the SGOC with different proportions of cases and have the increased As, Cr, and Pb contents relative to the maximum permissible concentration of soils. Clustering of the data shows the presence of two clusters, which indicate the availability of the background and anomalous values associated with the technogenic impact of the mining industry in the study area of the Sarala gold ore cluster.